(untitled) (Web of Teachers: Inderscience Research, 2024)
The article put forward ideas on the development of human potential by qomusi scholars of the East. In particular, it was noted by allomas that the development of intelligence, thinking and talent in a person is a determining factor I. At the same time, moral progress in human maturation indicates that it is a factor that determines its mental potential.